Evaluation of Cases with Hydatid Cyst Who Presented with Pulmonary Symptoms - Özgül Yiğit; Mehmet Toksöz; Seyithan Özaydın (Haseki Tıp Bülteni, 2015)
Aim: Hydatid disease is a parasitic infection caused by Echinococcus granulosus. The lungs are the most common affected organs in children. Hydatid disease can appear with nonspecific symptoms such as cough, chest pain and hemoptysis. Radiological findings are important in the diagnosis of the disease. In this article, we report ten patients who presented with nonspecific pulmonary symptoms. Methods: We included 10 patients (age range: 4-15 years) who attended our pediatrics outpatient clinic with the diagnosis of hydatid disease between May 2011 and May 2012. We analyzed the data on age, gender, primary complaint, clinical features, diameter and location of the cysts, and history of contact with animals. Hydatid cysts were diagnosed by imaging techniques and serologic tests. Results: The most common symptoms were coughing, chest pain, weakness, dyspnea, fever, and hemoptysis. In five patients, the cysts were located in the right lung; in four patients, the cysts were located in the left lung, and in the remaining patient, the cysts were bilateral. The diameters of the lung cysts were between 5 and 13 cm. Five of ten patients had both lung and liver cysts. Complications were observed in five patients. In eight patients, serologic tests results were positive. Five patients had a history of previous contact with animals. The patients were operated in the pediatric surgery unit. Conclusion: Hydatid disease is endemic in Turkey. Disease awareness and knowledge in children and their families is of great importance for the prevention of hydatid disease. (The Medical Bulletin of Haseki 2015; 53: 147-52)